One-stage microwave-assisted activated carbon preparation from Langsat peel raw material for adsorption of iron, manganese and copper from acid mining waste - Ni'mah, Lailan; Juliastuti, Sri Rachmania; Mahfud, Mahfud (Communications in Science and Technology, 2023)
This study describes the efficacy of microwave technology for the preparation of an activated carbon from Lansium domesticum peel as an adsorbent to adsorb Fe, Cu, and Mn from acid mine waste. In contrast to the conventional pyrolytic carbonization technique, the described method demonstrated several unparalleled advantages, including superior energy efficiency and remarkably rapid processing. The reported microwave irradiation method was able readily to achieve a morphology and extensive surface area similar to that of a sample produced using the traditional pyrolytic carbonization method for 2 hours, and this was accomplished in just 10 minutes. The activated carbon obtained was characterized using SEM-EDX, BET-BJH, and proximate test and applied to adsorb metal ions from acid mine waste to evaluate the isothermal adsorption model. The best power for activated carbon production was 400 watts for 10 minutes, which met the requirements of ASTM D 4607 for determining the iodine value of activated carbon. Optimal mass for adsorbing Fe, Cu, and Mn from acid mine waste was 4 grams with the removal percentages of 94.08%, 83.69%, and 90.67%, respectively. BET surface area was 1367.0385 m2/g along with a BJH cumulative volume and an average pore diameter of 1.112 cm3/g and 2.25 nm, respectively. This suggests that it possesses mesoporous characteristics and adheres to the Langmuir model during the adsorption process, signifying monolayer adsorption. Meanwhile, kinetics followed the pseudo-second-order rate equation.